Sudden Cardiac Death: The Most Feared but Potentially Preventable Presentation of Wolff-Parkinson-White Syndrome - Ana Rita Pereira; Alexandra Briosa; Rita Miranda; Sofia Sequeira Almeida; Luís Brandão; Hélder Pereira (Case Reports in Cardiology)
Background. Wolff-Parkinson-White syndrome is an uncommon cardiac disorder characterized by the presence of one or more accessory pathways that predispose patients to frequent episodes of arrhythmias. The prognosis is usually good, but there is a lifetime risk of malignant arrhythmias and sudden cardiac death. Case Summary. A 25-year-old male presented a witnessed out-of-hospital cardiac arrest with ventricular fibrillation rhythm. Due to rapid initiation of prehospital advanced life support, return of spontaneous circulation was observed. During the transport to the hospital, an irregular wide complex tachycardia suggestive of preexcited atrial fibrillation with haemodynamic instability was also observed and a synchronized shock was applied. Baseline 12-lead electrocardiogram was compatible with sinus rhythm and ventricular preexcitation pattern. After clinical stabilization, an electrophysiological study was performed confirming the presence of a left anterolateral accessory pathway with a short antegrade effective refractory period. Successful radiofrequency catheter ablation was achieved. Discussion. The reported clinical case recalls fundamental features of the Wolff-Parkinson-White syndrome and outlines the increasing evidence and importance of the invasive risk stratification and even catheter ablation in asymptomatic patients who suffer from this uncommon disease that may have a dramatic and fatal initial clinical manifestation.